Digital Marketing Strategy Based On E-Service, Brand Image And Reviews For Gofood MSMEs - Azlan Azhari; Abdul Rahman; Deddy Ibrahim Rauf (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
This study aims to determine the effect of E-Service Quality, Brand Image, and Online Customer Reviews on Online Purchasing Decisions at Almaz Fried Chicken on the GoFood platform. The sampling method used in this study is a non-probability sampling approach with the Accidental Sampling technique, which is a sampling technique based on chance, where anyone who accidentally meets the researcher can be used as a respondent if deemed suitable as a data source. The number of respondents in this study was 96 people who were consumers who had made online purchases at Almaz Fried Chicken through the GoFood application. The data obtained were analyzed using the SPSS 25 application with multiple linear regression analysis methods. The partial results of the study indicate that E-Service Quality has a positive and significant effect on Online Purchasing Decisions, which means that the better the quality of electronic services provided, the higher the consumer's decision to make a purchase. Furthermore, Brand Image also has a positive and significant effect on Online Purchasing Decisions, which shows that a strong and positive brand image can increase consumer trust and purchasing interest. In addition, Online Customer Reviews have a positive and significant effect on Online Purchasing Decisions, which means that the more positive reviews given by customers, the greater the tendency of other consumers to make a purchase. Simultaneously, the three variables e-service quality, brand image, and online customer reviews have a positive and significant influence on online purchasing decisions for Almaz Fried Chicken on GoFood. These results indicate that good digital service quality, a strong brand image, and positive customer reviews are a crucial combination in improving consumer purchasing decisions in the digital era.